Spatial variability of eucalyptus dendrometric properties and chemical attributes of a Quartzarenic Neosol - Lima, Elizeu de Souza; Montanari, Rafael [UNESP]; Lovera, Lenon Henrique [UNESP]; Minhoto Teixeira Filho, Marcelo Carvalho [UNESP]; Paz Gonzalez, Antonio (Univ Estadual Mato Grosso Sul, 2017)
The generation of large quantities of solid waste and effluents from pulp and paper industry has made environmental worry. This study aimed to analyze the linear correlations of individual development of Eucalyptus urograndis trees depending on the chemical properties of a Quartzarenic Neosol, in order to highlight specific areas of closely managing associated with the development of eucalyptus in order to use the lime sludge extraction cellulose in the form of sustainably fertilizer to the environment. An experimental grid approximately 2,0 h was installed containing 50 sampling points in a Quartzarenic Neosol and then collected plant attributes and soil for the determination of chemical parameters in the layers of 0-0.20 and 0.20-0.40 m municipality Trs Lagoas (MS). The results were analyzed by classical statistical and geostatistical. The spatial dependence varies according to the assessed chemical attributes and depth collection. In the vertical variability, there are also horizontal variations among the depths, since for the same nutrient scope was different between the sampled layers.
Keywords: cellulosic waste forest sustainability; oxyfertil; geostatistics